The relationship between psychopathic traits and executive functioning among incarcerated men - Aleija L. Rodriguez; Corey H. Allen; J. Michael Maurer; Bethany G. Edwards; Nathaniel E. Anderson; Carla L. Harenski; Michael R. Koenigs; Kent A. Kiehl; Kent A. Kiehl (Frontiers in Psychiatry)
Individuals with high levels of psychopathic traits are often characterized by behaviors suggesting attenuated executive functioning (EF); however, the literature examining these two constructs have provided varied results. The current study sought to clarify the relationship between EF and psychopathic traits in a large sample of incarcerated men (n = 811). We utilized the Hare Psychopathy Checklist - Revised (PCL-R) and the Delis-Kaplan Executive Function System (D-KEFS) to measure psychopathic traits and EFs, respectively. D-KEFS subtests included Verbal Letter Fluency, Tower Test, Color-Word Interference Test (CWIT), and Proverbs. Regression results showed that PCL-R Factor 1 scores (measuring interpersonal and affective traits) were positively associated with verbal fluency, verbal abstraction, and verbal inhibition ability. In addition, PCL-R Facet 4 scores (measuring antisocial traits) were negatively associated with performance on inhibitory EF tasks. Our findings help further clarify the relationships between specific psychopathic traits and forms of EF, and provide potential avenues for specialized treatment or intervention approaches targeting specific psychopathic traits.